Controladoria em instituições de microcrédito: um estudo de caso do programa Crediamigo do Banco do Nordeste do Brasil S/A (BNB) - Castelo, Joelma Leite (2005)
This work focusses on showing that the use of the Controllership in the financial institutions is capable to add value to its results, making the credit available, as a result, in the most appropriated way to benefit of the population, especially using the system of information presented by the Model of Economic Management (GECON). For the development of this study, a field research was fulfilled to analyze the Crediamigo Program of the northeast Bank of Brasil S.A., looking forward to know the description of the mentioned program, the products worked by it and the main obstacles faced. The research starts with the analysis of the Controllership, presenting its concept, purpose and tools, setting its importance in the current economic scene, contrasting to the traditional model of Accounting. After that, an analysis of the microcredit is made, with special attention for the emergence and development of the program of microcredit of the northeast Bank of Brasil S.A. - Crediamigo Program. Following this, an analysis of the model of managemental system based on the alluded program of microcredit, considering improvements to it, through the Controllership, especially using the tools of the Model of Economic Management (GECON), expecting to increase its level of effectiveness. This way, discoursing on the application of the Model of Economic Management (GECON) for the evaluation of the performance of the company, it is finally demonstrated, a hypothetical situation of its application in a banking institution, in which the improvements previously proposed are reached. It is noticed that the system of the Crediamigo Program can still improve, conceiving and managing a proper system of information of economic management, that makes it possible to the mentioned program evaluate if the determinated factors of its result had held as planned, or that possible effect will be able to provoke in the waited result to suffer alterations from course, allowing, thus, that the managemental decisions to be taken are adjusted, among the possible alternatives, making it possible, as a consequence, the achievement of a more efficient economic result, as well as the credit being used in the most apporiated way by the population.